2016
DOI: 10.1080/24701394.2016.1180512
|View full text |Cite
|
Sign up to set email alerts
|

DNA barcoding of three species ( Canis aureus, Canis lupus and Vulpes vulpes ) of Canidae

Abstract: Sequences of the mitochondrial cytochrome c oxidase subunit I (COI) gene have been used for DNA barcoding and determining the genetic diversity of mammal species. In the current study, our intention was to test the validity of COI barcodes for detecting genetic divergence and to reveal whether or not there is a genetic variation at this marker within canids. Three species (Canis aureus, Canis lupus and Vulpes vulpes) from the family Canidae were selected for DNA barcoding using samples collected from Iran and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…3 species of Canidae, one of the most interesting families of Mammalia, which is threatened due to illegal poaching, poisoning, and habitat loss, have been explored by DNA barcoding approach to validate COI barcode and detect genetic divergence. The mean sequence divergence among and within species was 12.32% and 0.61% respectively indicating relatively higher genetic diversity than previously reported studies (Aksöyek et al, 2017). The consistency between DNA barcoding and morphological identification for a particular species depends on the presence or absence of sibling species that are morphologically and genetically similar.…”
Section: Dna Barcoding In Animalsmentioning
confidence: 61%
“…3 species of Canidae, one of the most interesting families of Mammalia, which is threatened due to illegal poaching, poisoning, and habitat loss, have been explored by DNA barcoding approach to validate COI barcode and detect genetic divergence. The mean sequence divergence among and within species was 12.32% and 0.61% respectively indicating relatively higher genetic diversity than previously reported studies (Aksöyek et al, 2017). The consistency between DNA barcoding and morphological identification for a particular species depends on the presence or absence of sibling species that are morphologically and genetically similar.…”
Section: Dna Barcoding In Animalsmentioning
confidence: 61%
“…Furthermore, Aksöyek et al. () and İbiş et al. () suggested the occurrence of a distinct mitochondrial lineage for the Turkish red fox ( Vulpes vulpes ) from this region.…”
Section: Discussionmentioning
confidence: 98%
“…Although studies have considered the potential role of Anatolia as a glacial refugium for some species (Bilgin, ; Hewitt, ), phylogeographical analyses related to the potential refugia in the Anatolian region are scarce. Molecular studies on the mammal species distributed in Turkey, such as rodents, carnivores and some insectivores, have suggested that these populations harbour unique genetic lineages, either in terms of haplotypes or evolutionarily significant units (Aksöyek, İbiş, Özcan, Moradi, & Tez, ; Bannikova et al., ; Dubey, Diker, Kurtonur, & Vogel, ; Dubey et al., ; Gündüz, Rambau, Tez, & Searle, ; Gündüz et al., , ; İbiş, Aksöyek, Özcan, & Tez, ; İbiş, Tez, & Özcan, ; İbiş et al., ; Neumann et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…The number of direct and indirect scientific studies conducted on the jackal in Turkey is limited. Aksöyek (2015) conducted a master's thesis on DNA barcoding for the identification of 3 Canidae species (wolf Canis lupus, jackal and fox Vulpes vulpes) distributed in Turkey. İbiş et al (2015) performed phylogenetic studies on the jackal that were based on D-loop sequences.…”
Section: Introductionmentioning
confidence: 99%